Social media as a means to access millennial wine consumers. Issue 3 (21st August 2017) - Fuentes Fernández, Rosana; Vriesekoop, Frank; Urbano, Beatriz
Abstract : Purpose: The purpose of this paper is to gain insights of the use of social media (SM) in the wine industry. The theoretical viewpoint is to analyse wineries' SM segmentation, targeting and positioning (STP) to help the wine industry to improve the effectiveness of SM communication. Design/methodology/approach: An observational study of Spanish wineries' SM presence and traffic was carried out during a three-month period in 2013 and repeated in 2016. During this period, a questionnaire was distributed to 196 wineries. Logistic regression was used to model the dichotomous outcome variable of whether a winery "does" or "does not" utilise SM. Additionally, leader wineries were interviewed in April/May 2016 about SM STP. Findings: The results show that most wineries are starting in SM without a well-defined strategy. The presence of a webpage is significantly related to the use of SM. SM wineries do not segment and can take advantage of digital targeting strategies. Practical implications: Segmentation and targeting SM can improve the effectiveness of the winery SM activities as well as the winery competitiveness in the wine industry. Originality/value: This paper is a first step in understanding the value of segmentation SM to reach millennial consumers and the importance of targeting to improve the effectiveness of winery on SM.